Unexpected duodenopancreatectomy in an "awake" gastrectomized patient: Case report and technical notes. (April 2021) - Papagni, V.; Piacente, C.; Varvara, M.; Vincenti, L.
Highlights: A patient with a previous history of gastric cancer was admitted to our unit with fever and jaundice. Preoperative evaluation showed the presence of calculi of the common bile duct (CBD). During the preoperative anaesthetic evaluation, neuraxial-type anaesthesia was proposed given the patient's frailty. Exploration of the CBD revealed neoplastic tissue involving the ampulla of Vater. A duodenopancreatectomy was performed under neuraxial anaesthesia. A modified reconstruction was performed, and a mechanical stapler for hepaticojejunal (HJ) anastomosis was used. The outpatient follow-up showed physical recovery of the patient with a resumption of appetite and weight gain, and HJ anastomosis showed no stricture during the MRI performed 5 months after the operation. Abstract: Introduction and importance: Early diagnosis, surgical techniques and adjuvant therapy in patients undergoing gastrectomy for cancer have prompted an increase in the number of long-term surviving patients. The detection of pancreatic head tumours in patients undergoing gastrectomy is challenging, even for expert surgeons. Case presentation: A 78-year-old woman presented with a previous history of gastric cancer treated 2 years before D2 total gastrectomy and Roux-an-Y reconstruction. The patient reported uneven tissue located on the head of the pancreas 6 months after the operation. MRI showed dilation of the intrahepatic bile ducts and common bile duct stones. During the preoperative evaluation, neuraxial-type anaesthesia was proposed to the patient given her frailty. After choledochotomy, solid tissue involving the ampulla of Vater was found. Although not originally planned, a duodenopancreatectomy (DP) was performed under neuraxial anaesthesia. Clinical discussion: The approach to DP in patients with a history of gastrectomy and Roux-en-Y reconstruction requires a modified surgical approach, which is not standardized. Other cases of DP performed on patients under neuraxial anaesthesia are not described in the literature. Performing a modified reconstruction, we can reduce the number of intestinal anastomoses and the risk of anastomotic dehiscence. The choice of neuraxial anaesthesia has been demonstrated to be a suitable solution for the patient with rapid recovery. Conclusion: In our experience, DP is a safe and feasible procedure in gastrectomized patients. Mechanical hepaticojejunal (HJ) anastomosis is a possible alternative to traditional manual anastomosis. Neuraxial anaesthesia in selected patients can be considered a safe practice for rapid postoperative recovery compared to general anaesthesia.